Tabu search for vehicle routing problem with stochastic demands - Irhamah, 1978-, author; Zuhaimy Ismail; International conference on Research and Education in Mathematics (3rd : 2007 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2007)
Bibliography: p. 5.